Under sleeper pads in transition zones at railway underpasses: numerical modelling and experimental validation - Ribeiro , C. (2014)
In railway lines, transition zones between different track support conditions normally evidence higher degradation rates, thus requiring additional maintenance to ensure safety and service quality. Studies based on numerical simulations indicate that under sleeper pads (USP) can minimise those degradation rates. The study presented herein focuses on the inﬂuence of USP on the dynamic behaviour of transitions to underpasses, in an attempt to ﬁll the gap between numerical and ﬁeld studies. To that aim, the authors used ﬁnite element method models, calibrated and validated with ﬁeld measurements. These models take into account the train–track interaction and include all relevant track components and backﬁll geomaterials. This study shows that soft USP have a signiﬁcant inﬂuence over the track’s dynamic behaviour: amplifying rail displacements and sleeper accelerations, and inducing abrupt variations in the track vertical stiffness and oscillations in train–track forces. To beneﬁt from the use of USP, the authors highlight the need to carefully design stiffness properties of USP and determine their arrangement at transitions. An improved design for the transition zone is proposed.